Ciclo alfabetização: as propostas e as práticas pedagógicas - Arnosti, Vanessa Bueno [UNESP] (2013)
Given the scale of social and educational problems that mark access to reading and writing by the Brazilian population, this dissertation is focused on the literacy cycle. According to the legislation, this cycle covers the first three years of primary school and involves changes in school work. These transformations imposed by the changes of the elementary school curriculum as a whole, resulting from the one-year increase in duration with the anticipation of registration compulsory for 6 years. In practice, this involves the extension of the legal time devoted to literacy and education for young children, before served by infant education. Official documents recommend that schools develop different teaching methods from traditional to welcome the perspectives and interests of children, respecting the cultural differences between them. The proposals advocate the involvement of students in the practices of reading and writing, seen as crucial to the success of learning. To understand what happens in reality, with education, literacy in this cycle, we examined the documents of Federal Legislation and containing guidelines proposed by the Education Department of the county and the management plans of the participating schools where we conduct field research. Considering that the educational practices are based, implicitly or explicitly, in different conceptions of teaching and learning of reading and writing were conducted classroom observations and interviews with teachers in two schools with the highest and two schools with the lowest averages in assessing performance of students in the last three years. These schools were selected 3 classes (one of each series) totaling 12 classes and their teachers to participate. The results show that educational policies are justified by the democratization of education, but ignore history and reality of the institutions to which they refer. The results reveal the occurrence of a few changes in literacy...